Teknologi Ground Plane Augmented Reality Pengenalan Daur Ulang Limbah : Augmented Reality Ground Plane Technology Introduction to Waste Recycling - Erick Merpati; Virginia Tulenan; Henry Valentino F. Kainde (Universitas Sam Ratulangi, 2024)
Waste is leftover material in an activity and/or production process. Excessive and unmanaged waste will cause environmental pollution. We can also feel environmental pollution in the environment around us. The government of course has tried to minimize the problem of waste which is the cause of environmental pollution. However, public awareness plays an important role in protecting the environment. Of the various ways that can be done to overcome the problem of accumulated waste, one of the things we can do is recycling. This research was made to introduce recycling. With the help of augmented reality technology, people can learn about waste recycling in a more efficient and interesting way. This Waste Recycling Introduction Application will be made using Unity and the Vuforia SDK, where one of Vuforia's features, namely the Ground Plane, allows users to place digital content on a horizontal surface in the surrounding environment, such as a floor or table. The development method that I use is the Multimedia Development Life Cycle. This research will produce an Augmented Reality application that introduces waste recycling which is expected to increase public awareness of recycling which can be done to reduce the impact of environmental pollution.